Pemantauan Perubahan Deformasi Tanah Tahun 2014–2024 Berbasis DInSAR di Kecamatan Cisarua - Amaanah, Annisa; Sulastri, Ai; Alfarezy, Alif; Pitaloka, Ghea Redana; Anam, Khairul; Aliyan, Silmi Afina (PT. Pubsains Nur Cendekia, 2025)
Cisarua District, situated on the Lembang Fault line, has a high risk due to its proximity to densely populated settlements and its potential for large-magnitude earthquakes. This study aims to analyze the deformation of the Lembang Fault in Cisarua District from 2014 to 2024 using Sentinel-1A and TerraSAR-X imagery data, as well as Digital Terrain Model (DTM) analysis from an Unmanned Aerial Vehicle, employing the high-resolution Differential Interferometric SAR (DInSAR) method. The deformation levels vary from low to high, with a dominance of moderate deformation levels. High deformation was identified on the north and northeast sides, adjacent to the active tectonic zone. The DTM analysis revealed a steep topographic gradient with an elevation of 975.9–1395 masl. The combination of deformation and steep topography indicates a significant risk of landslides. The results of this study are expected to assist in disaster mitigation in the Cisarua District due to the deformation of the Lembang Fault.